A comparison of diffusion tensor imaging tractography approaches to identify the Frontal Aslant Tract in neurosurgical patients - Kierońska-Siwak, Sara; Filipiak, Patryk; Jabłońska, Magdalena; Sokal, Paweł (Frontiers in Neuroscience, 2025)
IntroductionThis study aims to present various tractography methods for delineating the Frontal Aslant Tract (FAT) and to quantify morphological features of FAT based on diffusion tensor imaging.MethodsThe study includes 68 patients, for which FAT was reconstructed using the Region Of Interest (ROI)-based approach. The ROIs were defined in either SFG – Superior Frontal Gyrus (ROI 1), or SMA—Supplementary Motor Area (ROI 2). The respective endpoints were located in the Inferior Frontal Gyrus (IFG)—either in pars opercularis or in pars triangularis. For each patient, FAT was delineated using four combinations of the above ROI–endpoint pairs.ResultsThe highest streamline counts and fiber volumes of FAT were obtained using ROI 1 (i.e., SFG) with the endpoint in IFG pars opercularis. All subjects expressed left dominance of the pathway quantified by the higher streamline counts and fiber volumes regardless of gender. Additionally, higher Mean Diffusivity (MD) and lower Fractional Anisotropy (FA) values were observed in patients above 55 years of age than in younger patients.DiscussionFAT is a neural pathway that can be tracked based on various anatomical landmarks. Clinically, it appears that delineating FAT between SFG and the pars opercularis region of IFG is optimal, as it is directly associated with the highest number of fibers and the greatest volume of the tract contained between these points.